Evaluasi Layanan Mooc Aplikasi Pintar Menggunakan Framework ITIL V4 Pada Pusdiklat Teknis Kemenag Sumbar - Faiz, Muhammad Raja; Ananda, Rifki; Aprialsyah, Muhammad Syahril; Sularno, Sularno (CV. Information Technology Training Center - Indonesia (ITTC), 2024)
This research aims to evaluate the effectiveness of the PINTAR application, a Massive Open Online Course (MOOC) platform designed to support the training of State Civil Apparatus (ASN) within the West Sumatra Ministry of Religion. Using the ITIL V4 framework, this research assesses service quality, user satisfaction levels, and identifies areas that require improvement to ensure applications can provide optimal benefits. Evaluation is carried out through direct observation of application use, in-depth interviews with stakeholders, and distributing questionnaires to users. The research results show that the PINTAR application has met most of the service quality standards, especially in terms of accessibility, relevance of training materials and interactive features offered. However, there are several weaknesses that need to be corrected, such as limited transparency in managing user data, a lack of regular service evaluations, and the responsiveness of technical support which is still not optimal. Users highly appreciate the time flexibility, ease of navigation, and interactive features such as learning simulations and live sessions with expert instructors. On the other hand, the survey also revealed the need to strengthen technological infrastructure and increase the competence of technical support teams to handle user complaints more effectively. By applying ITIL V4 principles, this research offers strategic recommendations for further development of the PINTAR application. Recommended improvement steps include increasing governance transparency, additional training for technical teams, development of more sophisticated reporting features, and regular evaluation of training materials. In conclusion, although the PINTAR application has made a significant contribution in supporting ASN training, continuous improvement efforts are needed to ensure this application can continue to be relevant and provide maximum added value for users.